2014
DOI: 10.3766/jaaa.25.2.8
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Middle Age on the Late Positive Component of the Auditory Event-Related Potential

Abstract: The middle-aged group showed substantially greater LPC peak amplitude in the frontal regions of the scalp than young adults. These results were in concert with N400 results, which suggested that the middle-aged group required more attentional/cognitive resources than young adults in order to maintain a high performance level on a linguistic task in the presence of competing linguistic stimuli (Davis et al, 2013).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 46 publications
3
11
0
Order By: Relevance
“…This suggests that it could also be related to response selection processes, that is, the comparison of the attended target location with stored memory of the possible speaker locations and/or the conscious decision for one of these locations. This interpretation is compatible with the hypotheses that the LPC reflects processes of context updating, target selection, and the allocation of attentional resources in stimulus-related processes (Davis & Jerger, 2014;Donchin, 1981;Kok, 2001;Polich, 2007) as well as semantic processing of linguistic stimuli (Juottonen et al, 1996). The fact that no correlation between LPCpc and behavioral performance was found may, on the other hand, argue against the possibility of a direct relation of this subcomponent to processes of focusing of spatial attention or-at least-against the possibility that these processes are directly related to localization accuracy.…”
Section: Lpcpcsupporting
confidence: 88%
See 1 more Smart Citation
“…This suggests that it could also be related to response selection processes, that is, the comparison of the attended target location with stored memory of the possible speaker locations and/or the conscious decision for one of these locations. This interpretation is compatible with the hypotheses that the LPC reflects processes of context updating, target selection, and the allocation of attentional resources in stimulus-related processes (Davis & Jerger, 2014;Donchin, 1981;Kok, 2001;Polich, 2007) as well as semantic processing of linguistic stimuli (Juottonen et al, 1996). The fact that no correlation between LPCpc and behavioral performance was found may, on the other hand, argue against the possibility of a direct relation of this subcomponent to processes of focusing of spatial attention or-at least-against the possibility that these processes are directly related to localization accuracy.…”
Section: Lpcpcsupporting
confidence: 88%
“…The LPC is usually found to be maximal over parietal scalp areas and is assumed to reflect various cognitive processes, such as decision making and target selection (Kok, 1997;Picton, 1992), context updating, explicit memory, and recollective processes, as well as evaluation and processing of stimulus meaning (Juottonen, Revonsuo, & Lang, 1996). The LPC has also been observed in a multispeaker word-pair semantic categorization task, in which listeners responded to an attended stream of words while ignoring competing speech from a different location (Davis & Jerger, 2014). Interestingly, an increased LPC has been observed after a spatial switch in the position of a target speaker, relative to a situation in which the target speaker did not change position (Getzmann, Hanenberg, Lewald, Falkenstein, & Wascher, 2015).…”
mentioning
confidence: 99%
“…obtained from a word-pair semantic categorization task with simultaneously presented competing speech (Davis and Jerger, 2014). The middle-aged group performed the task as successful as the young group, but had significantly greater LPC amplitudes at frontal sites.…”
Section: Effects Of Task Difficultymentioning
confidence: 93%
“…Results from this study indicated that both groups were z9% more accurate for No Match conditions and had faster reaction times for Match conditions. No behavioral age-related differences in accuracy or reaction time were observed between YAs and middle-aged adults, although the late positive component of the AERP showed group differences in scalp topography, indicating that middle-aged adults recruited additional (i.e., frontal) regions of the brain to successfully complete the task (Davis and Jerger, 2014).…”
Section: Linguistic Processing Tasksmentioning
confidence: 78%